2021
DOI: 10.16910/jemr.13.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic subvocalization: An eye-tracking study on silent poetry reading

Abstract: The present study investigates effects of conventionally metered and rhymed poetry on eye-movements in silent reading. Readers saw MRRL poems (i.e., metrically regular, rhymed language) in two layouts. In poem layout, verse endings coincided with line breaks. In prose layout verse endings could be mid-line. We also added metrical and rhyme anomalies. We hypothesized that silently reading MRRL results in building up auditive expectations that are based on a rhythmic “audible gestalt” and propose that rhythmicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 137 publications
1
6
0
Order By: Relevance
“…We note that the depth of our analyses was constrained by the amount of available data, which, in turn, was partly determined by the limited availability of professional poets as participants. Hence, the data at hand did not support complex statistical models including, for instance, more text-structural variables that have been shown to affect poetry reading (Beck & Konieczny, 2021;Menninghaus & Wallot, 2021). To better assess whether poetic structure (e.g., stanza form or systematic rhyme) differentially affects poetry reading in expert-and novice readers, care should be taken in future investigations that each reader is presented with a sufficient number of texts.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We note that the depth of our analyses was constrained by the amount of available data, which, in turn, was partly determined by the limited availability of professional poets as participants. Hence, the data at hand did not support complex statistical models including, for instance, more text-structural variables that have been shown to affect poetry reading (Beck & Konieczny, 2021;Menninghaus & Wallot, 2021). To better assess whether poetic structure (e.g., stanza form or systematic rhyme) differentially affects poetry reading in expert-and novice readers, care should be taken in future investigations that each reader is presented with a sufficient number of texts.…”
Section: Discussionmentioning
confidence: 96%
“…Including main and interaction effects of text-and line position allowed us to approximate how participants navigated through the poems. Although this is, admittedly, a crude approximation that reduces texts to a linear sequence of words and disregards most of the text structure, e.g., the division of poems into lines and stanzas (Beck & Konieczny, 2021;Fechino et al, 2020;Menninghaus & Wallot, 2021), we refrained from including further structure-related variables, since the available data did not support overly complex models; higher-order interactions were excluded for the same reason. We then eliminated non-significant predictors from the initial base model in a stepwise fashion, using a liberal alpha level of p < .1.…”
Section: Discussionmentioning
confidence: 99%
“…Although eye-tracking studies have indicated that reading times and fixations are influenced by word properties, such as frequency or sonority (Xue et al, 2019), evidence has been found for rhythmic subvocalization during silent reading (Beck & Konieczny, 2020). This suggests that the internal rhythm of a poem might be indeed simulated through auditory imagery.…”
Section: Associations Between Reader Characteristics and Poetry-elici...mentioning
confidence: 99%
“…Although there is a substantial body of research on measuring the effect of SLS on reading using standardized tests, eye-tracking studies that focus on the development of reading skills are uncommon (Schroeder et al, 2015). Studies have examined gaze patterns while reading text or phrases (Beck & Konieczny, 2020;Geyer et al, 2020;Magyari et al, 2020). Smyrnakis et al (2021) compared the silent and loud reading ability of typical and dyslexic readers using eye-tracking while Faber et al (2020) investigated the differences in stable eye movement patterns during narrative reading.…”
Section: Related Workmentioning
confidence: 99%